Magnetoliposomes as model for signal transmission - G. R. Barreto; C. Kawai; A. Tofanello; A. A. R. Neves; J. C. Araujo-Chaves; E. Belleti; A. J. C. Lanfredi; F. N. Crespilho; I. L. Nantes-Cardoso (Royal Society Open Science, 2019)
Liposomes containing magnetic nanoparticles (magnetoliposomes) have been extensively explored for targeted drug delivery. However, the magnetic effect of nanoparticles movement is also an attractive choice for the conduction of signals in communication systems at the nanoscale level because of the simple manipulation and efficient control. Here, we propose a model for the transmission of electrical and luminous signals taking advantage of magnetophoresis. The study involved three steps. Firstly, magnetite was synthesized and incorporated into fusogenic large unilamellar vesicles (LUVs) previously associated with a fluorescent label. Secondly, the fluorescent magnetite-containing LUVs delivered their contents to the giant unilamellar vesicles (GUVs), which were corroborated by magnetophoresis and fluorescence microscopy. In the third step, magnetophoresis of magnetic vesicles was used for the conduction of the luminous signal from a capillary to an optical fibre connected to a fluorescence detector. Also, the magnetophoresis effects on subsequent transmission of the electrochemical signal were demonstrated using magnetite associated with CTAB micelles modified with ferrocene. We glimpse that these magnetic supramolecular systems can be applied in micro- and nanoscale communication systems.